Prevalence of Hyperthyroidism in Patients with Atrial Fibrillation - Inam Ullah, Shakir Ghaffar, Muhammad Ilyas, Falak Zeb, Sulaiman Tahir, Muhammad Haidar Zaman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hyperthyroidism causes a rise in cardiovascular disease and dysrhythmias, leading to increased mortality. Low serum thyrotropin levels are a known independent risk factor for atrial fibrillation (AF). The frequency of hyperthyroidism in patients with AF is still unknown. Objectives: To determine the prevalence of hyperthyroidism in patients with AF admitted to a tertiary care hospital in Peshawar. Methodology: This was a cross sectional observational study that included 155 patients with AF. The study was conducted in the cardiology department of a tertiary care hospital in Peshawar, Pakistan, from December 2019 to May 2020. Results: Hyperthyroidism was found in 13(8.39%) patients with atrial fibrillation, while 142(91.61%) patients were without hyperthyroidism. There were 94 (60.65%) males and 61(39.35%) females. The ratio of male to female was 1.6: 1. The mean age of the patients enrolled was 50.35 years+14.95SD, with a range of 18-75 years. Patients were divided into three age groups, and atrial fibrillation was common in the 41-60 (years) age group. Conclusion: Hyperthyroidism is a recognized cause of atrial fibrillation. Every new-onset atrial fibrillation should be investigated with serum TSH levels. It can result in cerebral embolic episodes, particularly in the elderly and people with other risk factors. Keywords: Atrial fibrillation, Hyperthyroidism, Arrhythmia